Spruce versus Arabidopsis: different strategies of photosynthetic acclimation to light intensity change - Štroch, Michal; Karlický, Václav; Ilík, Petr; Ilíková, Iva; Opatíková, Monika; Nosek, Lukáš; Pospíšil, Pavel; Svrčková, Marika; Rác, Marek; Roudnický, Pavel; Zdráhal, Zbyněk; Špunda, Vladimír; et al. (Photosynthesis research, 2022)
The acclimation of higher plants to different light intensities is associated with a reorganization of the photosynthetic apparatus. These modifications, namely, changes in the amount of peripheral antenna (LHCII) of photosystem (PS) II and changes in PSII/PSI stoichiometry, typically lead to an altered chlorophyll (Chl) a/b ratio. However, our previous studies show that in spruce, this ratio is not affected by changes in growth light intensity. The evolutionary loss of PSII antenna proteins LHCB3 and LHCB6 in the Pinaceae family is another indication that the light acclimation strategy in spruce could be different. Here we show that, unlike Arabidopsis, spruce does not modify its PSII/PSI ratio and PSII antenna size to maximize its photosynthetic performance during light acclimation. Its large PSII antenna consists of many weakly bound LHCIIs, which form effective quenching centers, even at relatively low light. This, together with sensitive photosynthetic control on the level of cytochrome b6f complex (protecting PSI), is the crucial photoprotective mechanism in spruce. High-light acclimation of spruce involves the disruption of PSII macro-organization, reduction of the amount of both PSII and PSI core complexes, synthesis of stress proteins that bind released Chls, and formation of "locked-in" quenching centers from uncoupled LHCIIs. Such response has been previously observed in the evergreen angiosperm Monstera deliciosa exposed to high light. We suggest that, in contrast to annuals, shade-tolerant evergreen land plants have their own strategy to cope with light intensity changes and the hallmark of this strategy is a stable Chl a/b ratio.
Keywords: Cytochrome b6f Complex; cytochromy b; Picea; Photosystem I Protein Complex; Cytochromes b; Arabidopsis thaliana; Arabidopsis; chlorofyl a; Chlorophyll; smrk; Heat-Shock Proteins; Photoprotection; Chlorophyll A; fotosystém I (proteinový komplex); Light acclimation; Acclimatization; světlo; chlorofyl; Light-Harvesting Protein Complexes; Thylakoid membrane; Picea abies; Photosystem II Protein Complex; Photosynthetic control; Non-photochemical quenching; světlosběrné proteinové komplexy; komplex cytochromů b6f; Light; fotosystém II (proteinový komplex); aklimatizace; LHCII antenna; proteiny teplotního šoku